2019
DOI: 10.1186/s12881-019-0855-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel frame-shift deletion in FANCF gene causing autosomal recessive Fanconi anemia: a case report

Abstract: Background Fanconi anemia (FA) is a heterogeneous genetic disorder characterized by congenital anomalies, early-onset bone marrow failure, and a high predisposition to cancers. Up to know, different genes involved in the DNA repair pathway, mainly FANCA genes, have been identified to be affected in patients with FA. Case presentation Here, we report clinical, laboratory and genetic findings in a 3.5-year-old Iranian female patient, a product of a consanguineous marriage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…33–35 Frameshift indels can also act in a recessive way, where an accumulation of frameshift indels is necessary to induce a certain phenotype. 36 Our results indicate that FHM in patients without a mutation in CACNA1A , ATP1A2 and SCN1A is possibly caused by an accumulation of rare frameshift indels in multiple genes. This would mean that FHM is not always a dominantly inherited monogenic disease but is caused by the interaction of mutations in multiple genes with moderate effects.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…33–35 Frameshift indels can also act in a recessive way, where an accumulation of frameshift indels is necessary to induce a certain phenotype. 36 Our results indicate that FHM in patients without a mutation in CACNA1A , ATP1A2 and SCN1A is possibly caused by an accumulation of rare frameshift indels in multiple genes. This would mean that FHM is not always a dominantly inherited monogenic disease but is caused by the interaction of mutations in multiple genes with moderate effects.…”
Section: Discussionmentioning
confidence: 63%
“…In rare cases, such proteins can, in an autosomal-dominant way, induce severe phenotypes, including neurological diseases 33–35. Frameshift indels can also act in a recessive way, where an accumulation of frameshift indels is necessary to induce a certain phenotype 36. Our results indicate that FHM in patients without a mutation in CACNA1A , ATP1A2 and SCN1A is possibly caused by an accumulation of rare frameshift indels in multiple genes.…”
Section: Discussionmentioning
confidence: 73%
“…There have been a limited number of reports on the genetic etiology of FA in populations from South Asia and the Middle East. Such studies have identified several novel disease‐causing germline genetic variants, including the first reports of FA caused by pathogenic variants in FANCO / RAD51C or FANCE (Aftab et al, 2017 ; Aslan et al, 2015 ; Aymun et al, 2017 ; Balta et al, 2000 ; Castella et al, 2011 ; de Winter et al, 2000 ; Donovan et al, 2019 ; Dorsman et al, 2007 ; Esmail Nia et al, 2016 ; Ghazwani et al, 2016 ; Gille et al, 2012 ; Kalb et al, 2007 ; Koc et al, 1999 ; Levran et al, 1997 ; Moghadam et al, 2016 ; Salem et al, 2014 ; Shahid et al, 2019 ; Shamseldin et al, 2012 ; Shukla et al, 2013 ; Solanki et al, , 2016 , 2017 ; Tamary et al, , 2000 , 2004 ; Vaz et al, 2010 ; Vundinti, 2014 ; Waisfisz et al, 1999 ; Wegner et al, 1996 ; Wijker et al, 1999 ; Zareifar et al, 2019 ) as well as discovery of a founder mutation in FANCL (Donovan et al, 2019 ), highlighting the importance of germline genetic studies of FA in underrepresented regions. In this report, we evaluated the genetic causes of FA in 19 patients from 17 unrelated families being considered for HCT in Pakistan and conducted a detail review of the causes of FA in South Asia and the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…Patients struggle with progressive bone marrow failure and severe hematological complications [24]. In addition, congenital malformations are also present [25,26]. All of these have been reported as germline mutations, resulting in an in-frame deletion of phenylalanine at a position that is conserved across species.…”
Section: Discussionmentioning
confidence: 99%
“…Patients struggle with progressive bone marrow failure and severe hematological complications [ 24 ]. In addition, congenital malformations are also present [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%